Validity and Reliability of Community Satisfaction Measurement Instrument in Health Care Institution - Deni Kurniadi Sunjaya (Jurnal Kesehatan Prima, 2021)
The Community Satisfaction Survey is mandatory based on Ministry of Administrative and Bureaucratic Reform Regulation number 14 in the year of 2017. An alternative measurement tool has been developed by expanding the measurement items. The research objective was to explore the validity and reliability of public satisfaction instruments in health institutions. The design was non-experimental, with a quantitative and cross sectional approach. The research was carried out in two entities, namely primary health care and hospital. Data collection using the IKM-29 questionnaire. Data processing with Rasch modeling and winsteps application. The results showed that the item reliability at PHC and hospital was 0.95 and 0.97 with Cronbach's alpha 0.95. The separation is more than 3 and the raw variance is more than 40%. In the two entities there are several different misfit items. Item 8 related to the perception of waiting time has a high degree of difficulty and is paradoxical. The results of the analysis show that the instrument is valid and reliable enough to be used as an alternative measurement of community satisfaction in PHC and Hospitals.